Serum 25-Hydroxyvitamin D3 and Mammography Density among Mexican Women. - Amina Amadou; Carine Biessy; Sabina Rinaldi; Veronika Fedirko; Nada Assi; Martin Lajous; Eduardo Ortiz-Panozo; Elsa Yunes; Ruy Lopez-Ridaura; Gabriela Torres-Mejia; Isabelle Romieu (PLoS ONE)
Low circulating levels of vitamin D and high mammographic density (MD) have been associated with higher risk of breast cancer. Although some evidence suggested an inverse association between circulating vitamin D and MD, no studies have investigated this association among Mexican women. We examined whether serum 25-hydroxyvitamin D3 [25(OH)D3] levels were associated with MD in a cross-sectional study nested within the large Mexican Teacher's Cohort. This study included 491 premenopausal women with a mean age of 42.9 years. Serum 25(OH)D3 levels were measured by liquid chromatography/tandem mass spectrometry. Linear regression and non-linear adjusted models were used to estimate the association of MD with serum 25(OH)D3. Median serum 25(OH)D3 level was 27.3 (23.3-32.8) (ng/ml). Forty one (8%) women had 25(OH)D3 levels in the deficient range (< 20 ng/ml). Body mass index (BMI) and total physical activity were significantly correlated with 25(OH)D3 (r = -0.109, P = 0.019 and r = 0.095, P = 0.003, respectively). In the multivariable linear regression, no significant association was observed between 25(OH)D3 levels and MD overall. However, in stratified analyses, higher serum 25(OH)D3 levels (≥27.3 ng/ml) were significantly inversely associated with percent MD among women with BMI below the median (β = -0.52, P = 0.047). Although no significant association was observed between serum 25(OH)D3 and percent MD in the overall population, specific subgroups of women may benefit from higher serum 25(OH)D3 levels.